Disaggregating Okun's law: decomposing the impact of the expenditure components of GDP on euro area unemployment - Robert Anderton; Ted Aranki; Boele Bonthuis; Valerie Jarvis (European Central Bank (ECB), 2014)
This paper examines the usefulness of the Okun relationship as a “rule of thumb” for predicting changes in unemployment, as a result of changes in output. It argues that a disaggregated version of the Okun relationship – making use of the differential reaction of unemployment to changes in the various expenditure components of GDP - significantly enhances the capacity of the Okun relationship (in comparison to the aggregate “rule of thumb”) for predicting movements in unemployment. The paper tests this hypothesis using a dataset for the 17 euro area countries over the period 1996Q1-2013Q4. The results suggest that euro area unemployment is particularly sensitive to movements in the consumption component of GDP, while movements in foreign trade (exports and imports) have a much lower impact on unemployment developments. This reflects the highly labour-intensive nature of the services that represent the bulk of consumers' expenditure, while the higher productivity manufacturing-related content of exports tends to be less labour intensive.
Keywords: E2; E24; C23; 330; expenditure components of GDP; Okun relationship; panel econometrics; Unemployment